Acesso aberto na UFSCar: um estudo sobre a produção científica dos docentes dos Programas de Pós-graduação do CCET e CECH - Guirra, Daniel Andre Rigo (Universidade Federal de São Carlos, 2018)
A subject of constant discussions, scientific communication, since the seventeenth century, has been undergoing several changes. One of the most dramatic of those was from the middle of the last century with the emergence of the periodicals crisis, triggered by the explosion of the costs of subscriptions to international periodicals. In contrast, with the advent of the internet, STS studies, and also, the open access movement to scientific publications, new proposals begin to emerge, implying an open science and results available to all. On the other hand, research funding agencies have increasingly demanded that the researchers they fund publish in journals with a high impact factor, many of them, including paid access, generating future expenditures for the acquisition of journals by public libraries. As an example, only in 2017, the federal government in Brazil spent nearly 107 million dollars to maintain the CAPES Periodical Portal. Given the above, the aim of this research is to compare the methods of publication and knowledge dissemination by researchers and professors on the Postgraduate Programs in Exact Sciences (CCET) and Human Sciences (CECH) at UFSCar, and to verify what percentage of this output is in open access. Because it has a quantitative-qualitative research approach, this dissertation is composed of bibliographical research that brings together topics such as the scientific community, as well as communication among peers, their modes of production and scientific indicators. Finally, we discuss some topics relevant to postgraduate studies and the impact of their evaluation system. In the document research we use data from UFSCar, CV Lattes, Qualis CAPES and Sucupira Platform, adopting as a cut-off period the years 2013 to 2016 (last CAPES four-year evaluation). For the mapping of the bibliographic production of the researchers investigated here, we used the ScriptLattes software. With the data tabulated, we consulted which journals were registered in DOAJ and SciELO. For those which were not registered, we consulted the SHERPA / RoMEO database to verify the self-archiving policies of the journal titles identified. Finally, we researched articles from these journals on Google Scholar to see if they had copies available in open access repositories. The research results identified 19 programs, 434 teachers and the publication of 308 complete books, 1162 book chapters and 4638 scientific articles. From these, we find that the PGPs in the Exact Sciences have mostly male researchers, with predominant publication of articles in subscription scientific journals. On the other hand, in PGPs in the Humanities, there are more female teachers, with a higher percentage of publications in books (complete or chapters). Regarding the scientific articles, we could observe the predominance of publications in open access journals for programs in the Humanities. When accessing subscription journal articles on Google Scholar, we find the vast majority of them have open copies available. We conclude that our objectives have been met and we stress the importance of further studies on this theme.
Open access at UFSCar: a study on the scientific production of the professors of the Post-Graduation Programs of the CCET and CECH
Keywords: Acesso aberto; Produção acadêmica; Programas de Pós-graduação; Pesquisadores-docentes; Periódicos científicos; Open access; Academic production; Postgraduate programs; Researchers professors; Scientific journals; CIENCIAS HUMANAS; CIENCIAS SOCIAIS APLICADAS